Structural and Functional Analysis of Gly212 Mutants Reveals the Importance of Intersubunit Interactions in ASIC1a Channel Function - Bignucolo, Olivier; Vullo, Sabrina; Ambrosio, Nicolas; Gautschi, Ivan; Kellenberger, Stephan (Frontiers in Molecular Biosciences, 2020)
Acid-sensing ion channels (ASICs) act as pH sensors in neurons. ASICs contribute to pain sensation, learning, fear behavior and to neuronal death after ischemic stroke. Extracellular acidification induces a transient activation and subsequent desensitization of these Na+-selective channels. ASICs are trimeric channels made of identical or homologous subunits. We have previously shown that mutation of the highly conserved Gly212 residue of human ASIC1a to Asp affects the channel function. Gly212 is located in the proximity of a predicted Cl- binding site at a subunit interface. Here, we have measured the function of a series of Gly212 mutants. We show that substitution of Gly212 affects the ASIC1a pH dependence and current decay kinetics. Intriguingly, the mutations to the acidic residues Asp and Glu have opposing effects on the pH dependence and the current decay kinetics. Analysis of molecular dynamics simulation trajectories started with the coordinates of the closed conformation indicates that the immediate environment of residue 212 in G212E, which shifts the pH dependence to more alkaline values, adopts a conformation closer to the open state. The G212D and G212E mutants have a different pattern of intersubunit salt bridges, that, in the case of G212E, leads to an approaching of neighboring subunits. Based on the comparison of crystal structures, the conformational changes in this zone appear to be smaller during the open-desensitized transition. Nevertheless, MD simulations highlight differences between mutants suggesting that the changed function upon substitution of residue 212 is due to differences in intra- and intersubunit interactions in its proximity.